Pregnancy Outcomes in Women Aged 20–34 vs. ?35 Years: A Cross-Sectional Study in a Tertiary Referral Center - Farsyah Septrial Hendra Syahputra; Adhi Pribadi; Dini Hidayat; Eppy Darmadi Achmad; Andi Kurniadi (Indonesian Journal of Obstetrics and Gynecology, 2026)
Objective: This study aims to compare pregnancy outcomes between mothers under and over 35 years of age at Dr. Hasan Sadikin General Hospital. Methods: An observational analytic approach with a cross-sectional design was used. Data from the medical records of 150 patients at Dr. Hasan Sadikin General Hospital in 2022 were analyzed. Patients were divided into two groups: ages 20-34 and greater than or equal to 35. Data analysis was performed using SPSS version 27.0. Results: Advanced maternal age was significantly associated with mode of delivery [OR 2.16, 95% CI (1.08-4.28), p=0.048], hypertensive disorders of pregnancy [OR 3.99, 95% CI (1.86-8.38), p<0.001], and postpartum hemorrhage [OR 2.93, 95% CI (0.99-8.79), p=0.044]. Conclusion: This study affirmed that advanced maternal age is associated with adverse maternal outcomes, namely hypertensive disorders of pregnancy and postpartum hemorrhage. Moreover, compared to mothers aged 20-34, advanced maternal age is linked with higher rates of cesarean deliveries and forceps deliveries.   Keywords: Advanced maternal age pregnancy, Adverse maternal outcomes, Neonatal outcomes, Peak reproductive years, Complications of pregnancy